Kendali Glikemik pada Pasien Diabetes Melitus Tipe 2 dengan dan tanpa Tuberkulosis Paru - Wahiduddin Wahiduddin; Agung Pranoto; Sudjarwo Sudjarwo (Media Kesehatan Masyarakat Indonesia, 2019)
Glycemic control is important for people with diabetes mellitus (DM) because it has implications for effortsto manage DM. Pulmonary tuberculosis (PTB) is one of the many complications in DM patients associatedwith the process and results of treatment of the disease. The study aimed to determine glycemic control based onparameters of fasting blood glucose level (FBG), 2 hours post prandial blood glucose (2hPBG) and HbA1c in patientswith type 2 diabetes mellitus (T2DM) who had pulmonary TB. A cross-sectional study was conducted on 45T2DM subjects with PTB and 45 T2DM subjects without PTB who were outpatient in two hospitals in Surabaya.The results of the examination of FBG, 2hPBG, and HbA1c were analyzed descriptively, displayed in the form ofmean values and standard deviations (SD). The mean and SD were FBG (202.11 ± 78.68 mg/dl), 2hPBG (283.20± 107.20 mg/dl), and HbA1c (11.20 ± 2.61%) in T2DM subjects with pulmonary TB while subjects without pulmonaryTB were obtained FBG (175.29 ± 61.38 mg/dl), 2hPBG (208.22 ± 75.60 mg/dl), and HbA1c (9.34 ± 2.22%).The mean of FBG, 2hPBG and HbA1c of T2DM patients with pulmonary TB were higher than T2DM withoutpulmonary TB. This shows that the control criteria for DM that have not yet reached the target need to be done inan effort to better monitor glycemic control.